Low-loss integrated inductor and method of manufacturing the same

CN123017700APending Publication Date: 2026-10-30SHENZHEN GUDIAN ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611513050.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]本发明的主要目的是提供一种低损耗一体成型电感及其制备方法,旨在解决现有技术中一体成型电感耐高温性能不足、高温介电漂移、界面易失效及磁损耗高的技术问题

Benefits of technology

[0019]本发明中的技术方案通过在铁氧体磁粉表面依次形成硼-磷-镁复合无机钝化层和三元共聚的有机绝缘层;其中,无机钝化层作为非晶玻璃态膜层具有优异的绝缘性能和高温稳定性,有机绝缘层中富含刚性芳环结构,具有高玻璃化转变温度和优异的热稳定性,且高频下介电损耗低,纳米氧化锆和纳米氧化镁的高熔点和高绝缘性能有效抑制了高温条件下的介电漂移现象;因此,本发明中的一体成型电感具备在满足低损耗和高磁导率的前提下,在高温环境中具有更持久的使用寿命,满足车载电子和航空电子领域对高性能电感元器件的严苛要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a low-loss integrally-formed inductor and a preparation method thereof, and relates to the technical field of integrally-formed inductor manufacturing.The technical scheme in the application forms a boron-phosphorus-magnesium composite inorganic passivation layer and a ternary copolymer organic insulating layer on the surface of a ferrite magnetic powder in sequence; the inorganic passivation layer is an amorphous glass film layer with excellent insulation performance and high-temperature stability; the organic insulating layer is rich in rigid aromatic ring structures, has a high glass transition temperature and excellent thermal stability, and has low dielectric loss under high frequency; and the high melting point and high insulation performance of nano-zirconium oxide and nano-magnesium oxide effectively inhibit the dielectric drift phenomenon under high-temperature conditions; therefore, the integrally-formed inductor has a longer service life in a high-temperature environment under the premise of meeting the low loss and high magnetic permeability, and meets the stringent requirements of vehicle-mounted electronics and avionics on high-performance inductor components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of integral molded inductor manufacturing technology, and in particular to a low-loss integral molded inductor and its preparation method. Background Technology

[0002] Molded inductors are integral inductor devices manufactured by embedding a pre-wound coil body inside metal magnetic powder and then die-casting it. Compared with traditional power inductors, molded inductors have advantages such as structural stability, low impedance, good magnetic shielding, and high current tolerance. They can maintain excellent current stability in high-frequency and high-temperature environments, and are therefore widely used in automotive electronics, communication equipment, industrial power supplies, and consumer electronics. However, the magnetic core materials in related technologies are prone to cracking under long-term high-temperature operation, and another related technology suffers from significant permeability decay and loss spikes under high-temperature conditions. Developing a molded inductor that combines high temperature resistance, low loss, and high permeability has significant technological value and market implications. Summary of the Invention

[0003] The main objective of this invention is to provide a low-loss integrally molded inductor and its preparation method, aiming to solve the technical problems of insufficient high-temperature resistance, high-temperature dielectric drift, easy interface failure, and high magnetic loss in existing integrally molded inductors.

[0004] To achieve the above objectives, this invention proposes a low-loss integrally molded inductor, comprising a winding coil and a magnetic core encasing the winding coil. The magnetic core is obtained by composite material of metal magnetic powder and heat-resistant resin. The metal magnetic powder comprises ferrite magnetic powder and an inorganic passivation layer and an organic insulating layer sequentially coated on the surface of the ferrite magnetic powder. The organic insulating layer is obtained by copolymerization of styrene, N-phenylmaleimide, and fluorinated acrylate.

[0005] In one embodiment, the inorganic passivation layer is prepared by a passivation solution comprising the following raw materials in mass fractions: phosphoric acid: 8wt%–12wt%; boric acid: 3wt%–5wt%; light magnesium carbonate: 3wt%–5wt%; disodium EDTA: 0.5wt%–1wt%; and deionized water.

[0006] In one embodiment, the organic insulating layer comprises the following raw materials in parts by weight: styrene: 20 to 30 parts; N-phenylmaleimide: 30 to 40 parts; fluorinated acrylate: 10 to 20 parts.

[0007] Preferably, the molar ratio of N-phenylmaleimide to styrene is 1:1 to 1:2.

[0008] In one embodiment, the organic insulating layer further includes 3 to 7 parts by weight of zirconium-magnesium composite nanofiller. The zirconium-magnesium composite nanofiller comprises nano-zirconia and nano-magnesium oxide in a weight ratio of 3 to 8:1.

[0009] In one embodiment, the nano-zirconia has a particle size of 50 nm to 300 nm; and / or, the nano-magnesium oxide has a particle size of 50 nm to 300 nm.

[0010] In one embodiment, the heat-resistant resin comprises the following raw materials in parts by weight: o-cresol formaldehyde epoxy resin: 15 to 25 parts; epoxy modified silicone resin: 4 to 12 parts; aromatic amine latent curing agent: 2 to 4 parts; leveling agent: 0.5 to 1 part.

[0011] In one embodiment, the weight ratio of the metal magnetic powder to the heat-resistant resin is 8–10:2–3. Within this ratio range, the magnetic core possesses both sufficient mechanical strength and excellent magnetic properties.

[0012] In one embodiment, the particle size of the ferrite magnetic powder is 10 μm to 300 μm.

[0013] This invention also proposes a method for fabricating the low-loss integrally molded inductor as described above, comprising the following steps: S10. Immerse the cleaned and dried ferrite magnetic powder in a passivation solution for passivation treatment, then remove and dry it. S20. Styrene, N-phenylmaleimide, fluorinated acrylate, initiator and solvent are mixed and copolymerized to obtain a polymer liquid; then zirconium magnesium composite nanofiller is added, stirred, and then ferrite magnetic powder treated in step S10 is added. Part of the solvent is removed by rotary evaporation and then cured by heating to obtain metal magnetic powder. S30. Mix o-cresol formaldehyde epoxy resin, epoxy modified silicone resin, leveling agent and metal magnetic powder obtained in step S20 evenly, then add aromatic amine latent curing agent, stir, pour into mold and pre-cur and heat-cur, demold to obtain the low loss integral molded inductor.

[0014] In one embodiment, in step S10, the solid-liquid ratio of the passivation treatment is 1:4, the temperature is 50℃~60℃, the passivation time is 20min~30min, and after passivation, the product is dried at 80℃ for 2h~4h.

[0015] In one embodiment, during step S20, the copolymerization reaction is first kept at 70°C to 80°C for 2 to 3 hours, and then kept at 80°C to 90°C for 2 to 3 hours.

[0016] In one embodiment, in step S20, the heating and curing temperature is 110℃~120℃ and the curing time is 1h~2h.

[0017] In one embodiment, in step S30, the pre-curing temperature is 80℃~100℃ and the pre-curing time is 1h~3h; the heat curing temperature is 150℃~160℃ and the heat curing time is 1h~2h.

[0018] Preferably, in step S30, the die-casting pressure is 500MPa to 700MPa.

[0019] The technical solution of this invention involves sequentially forming a boron-phosphorus-magnesium composite inorganic passivation layer and a ternary copolymer organic insulating layer on the surface of ferrite magnetic powder. The inorganic passivation layer, as an amorphous glassy film, possesses excellent insulation performance and high-temperature stability. The organic insulating layer, rich in rigid aromatic ring structures, exhibits a high glass transition temperature and excellent thermal stability, with low dielectric loss at high frequencies. The high melting point and high insulation performance of nano-zirconia and nano-magnesium oxide effectively suppress dielectric drift under high-temperature conditions. Therefore, the integrally molded inductor of this invention, while meeting the requirements of low loss and high permeability, has a longer service life in high-temperature environments, satisfying the stringent requirements of automotive and aerospace electronics for high-performance inductor components. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.

[0022] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0023] This application proposes a low-loss integrally molded inductor, comprising a winding coil and a magnetic core encasing the winding coil, wherein the magnetic core is obtained by composite of metal magnetic powder and heat-resistant resin; the metal magnetic powder comprises ferrite magnetic powder and an inorganic passivation layer and an organic insulating layer sequentially coated on the surface of the ferrite magnetic powder; wherein the organic insulating layer is obtained by copolymerization of styrene, N-phenylmaleimide and fluorinated acrylate.

[0024] Specifically, the organic insulating layer in this invention is a terpolymer of styrene, N-phenylmaleimide, and fluorinated acrylate. N-phenylmaleimide (NPMI) is an excellent heat-resistant functional monomer. Due to the rigid structure of its intramolecular imide five-membered ring and benzene ring, copolymerizing it with monomers such as styrene can significantly improve the polymer's heat resistance. The introduction of fluorinated acrylate endows the copolymer with low surface energy and low dielectric constant, which helps reduce the dielectric loss of the insulating layer.

[0025] In a preferred embodiment, the molar ratio of N-phenylmaleimide to styrene in the organic insulating layer is 1:1 to 1:2. Within this ratio range, the copolymer exhibits a single glass transition temperature, resulting in a more uniform segmental structure and better compatibility.

[0026] In one embodiment, the inorganic passivation layer is prepared by a passivation solution comprising the following raw materials by mass fraction: orthophosphoric acid: 8wt%–12wt%; boric acid: 3wt%–5wt%; light magnesium carbonate: 3wt%–5wt%; EDTA-disodium: 0.5wt%–1wt%; and the balance being deionized water.

[0027] Specifically, by using the aforementioned passivation solution for passivation treatment, the resulting inorganic passivation layer is a boron-phosphorus-magnesium ternary composite amorphous glassy film. Orthophosphoric acid reacts with iron on the magnetic powder surface to form an iron phosphate passivation film. Simultaneously, the introduction of boric acid and magnesium salts ensures that the passivation film contains three active hydroxyl groups: B-OH, P-OH, and Mg-OH. During the subsequent organic insulating layer coating process, these three hydroxyl groups can form multiple hydrogen bonds and chemical bonds with the active groups in the organic insulating layer, significantly improving the interfacial bonding strength between the inorganic and organic layers and enhancing high-temperature reliability.

[0028] In one embodiment, the organic insulating layer comprises the following raw materials in parts by weight: Styrene: 20-30 parts; N-phenylmaleimide: 30-40 parts; Fluorine-modified acrylate: 10-20 parts.

[0029] Understandably, by further limiting the ratio of the above-mentioned polymer monomers, the polymer liquid obtained from the reaction has better coating properties on the surface of the magnetic powder, and the organic insulating layer obtained after curing is more uniform and dense, with better temperature resistance and insulation properties.

[0030] In one embodiment, the organic insulating layer further includes 3 to 7 parts by weight of zirconium-magnesium composite nanofiller; wherein the zirconium-magnesium composite nanofiller comprises nano-zirconia and nano-magnesium oxide in a weight ratio of 3 to 8:1.

[0031] It should be noted that both nano-zirconia and nano-magnesium oxide are inorganic oxide fillers with high melting points and high resistivity. When these two are compounded and dispersed in an organic insulating layer, their high temperature resistance enhances the overall thermal stability of the insulation layer, while their high insulation properties suppress dielectric drift under high-temperature conditions. Furthermore, the nanofillers act as physical cross-linking points during the curing process of the organic insulating layer, further improving the cross-linking density and dimensional stability of the organic insulating layer.

[0032] In one embodiment, the particle size of the nano-zirconia is 50 nm to 300 nm.

[0033] In one embodiment, the particle size of the nano-magnesium oxide is 50 nm to 300 nm.

[0034] In one embodiment, the weight ratio of the organic insulating layer to the ferrite magnetic powder is 0.5 to 1:1.

[0035] It should be noted that this embodiment further limits the ratio of organic insulating layer to ferrite magnetic powder, thus ensuring excellent insulation coating while minimizing the impact on the electromagnetic properties of the magnetic powder. If the proportion of organic insulating layer is too low, a continuous and dense insulating coating layer cannot be formed on the surface of the magnetic powder, resulting in insufficient insulation performance and increased core loss. If the proportion of organic insulating layer is too high, the volume of the non-magnetic organic insulating layer will be too large, significantly reducing the effective permeability of the magnetic core and increasing the manufacturing cost of the magnetic core.

[0036] In one embodiment, the heat-resistant resin comprises the following raw materials in parts by weight: o-cresol formaldehyde epoxy resin: 15 to 25 parts; epoxy modified silicone resin: 4 to 12 parts; aromatic amine latent curing agent: 2 to 4 parts; leveling agent: 0.5 to 1 part.

[0037] Specifically, o-cresyl formaldehyde epoxy resins possess a heat-resistant benzene ring backbone and multifunctional epoxy groups, exhibiting high crosslinking density and excellent heat resistance. The introduction of epoxy-modified silicone resins can improve the flexibility of the resin system and reduce curing stress. Simultaneously, the high-temperature stability of the silicone segments can further enhance the overall heat resistance of the magnetic core. Aromatic amine latent curing agents, such as diaminodiphenyl sulfone, contain rigid aromatic ring structures, and their cured products have significantly higher glass transition temperatures than conventional aliphatic amine curing systems.

[0038] In one embodiment, the weight ratio of the metal magnetic powder to the heat-resistant resin is 8-10:2-3.

[0039] It should be noted that if the proportion of heat-resistant resin is too low, the mechanical strength and insulation performance of the magnetic core will be insufficient; if the proportion of heat-resistant resin is too high, the permeability of the magnetic core will decrease significantly. Within the above-mentioned proportion range, the magnetic core can achieve both excellent mechanical and magnetic properties.

[0040] In one embodiment, the particle size of the ferrite magnetic powder is 10 μm to 300 μm.

[0041] This invention also proposes a method for fabricating a low-loss integrally molded inductor, comprising the following steps: S10. Immerse the cleaned and dried ferrite magnetic powder in a passivation solution for passivation treatment, then remove and dry it.

[0042] S20. Styrene, N-phenylmaleimide, fluorinated acrylate, initiator and solvent are mixed and copolymerized to obtain a polymer liquid; then zirconium magnesium composite nanofiller is added, stirred, and then ferrite magnetic powder treated in step S10 is added. Part of the solvent is removed by rotary evaporation and then cured by heating to obtain metal magnetic powder. S30. Mix o-cresol formaldehyde epoxy resin, epoxy modified silicone resin, leveling agent and metal magnetic powder obtained in step S20 evenly, then add aromatic amine latent curing agent, stir, pour into mold and pre-cur and heat-cur, demold to obtain the low loss integral molded inductor.

[0043] In one embodiment, in step S10, the solid-liquid ratio of the passivation treatment is 1:4, the temperature is 50℃~60℃, the passivation time is 20min~30min, and after passivation, the product is dried at 80℃ for 2h~4h.

[0044] By adopting the above technical solution, a uniform and dense boron-phosphorus-magnesium ternary composite amorphous glassy film can be formed on the surface of magnetic powder. If the temperature is too low or the time is too short, the passivation reaction will be incomplete and the film thickness will be insufficient. If the temperature is too high or the time is too long, the passivation layer may be too thick or crystallization may occur.

[0045] In one embodiment, during step S20, the copolymerization reaction is first kept at 70°C to 80°C for 2 to 3 hours, and then kept at 80°C to 90°C for 2 to 3 hours.

[0046] By adopting the above technical solution and employing a segmented heating polymerization process, it is beneficial to control the copolymerization reaction rate and the uniformity of the copolymer chain segment structure. In the copolymerization reaction, azobisisobutyronitrile (AIBN) or benzoyl peroxide (BPO) can be used as the initiator, with an amount of 0.5wt% to 1wt% of the total monomer mass. Butyl acetate, cyclohexanone, or dioxane can be used as the solvent.

[0047] In one embodiment, in step S20, after adding the zirconium-magnesium composite nanofiller, the mixture is stirred at high speed for 30 to 60 minutes to disperse the nanofiller uniformly in the polymerization liquid. Subsequently, passivated ferrite magnetic powder is added, and stirring continues for 20 to 40 minutes to ensure that the magnetic powder is fully wetted in the polymerization liquid.

[0048] In one embodiment, in step S20, after removing 60% to 80% of the solvent by rotary evaporation, the copolymer is heated to a curing temperature of 110°C to 120°C and a curing time of 1 to 2 hours to fully crosslink and cure the copolymer on the surface of the magnetic powder, forming a uniform and dense organic insulating layer.

[0049] In one embodiment, in step S30, the pre-curing temperature is 80℃~100℃ and the pre-curing time is 1h~3h; the heat curing temperature is 150℃~160℃ and the heat curing time is 1h~2h.

[0050] Preferably, in step S30, the die-casting pressure is 500MPa to 700MPa.

[0051] The technical solution of the present invention is further illustrated below through specific embodiments: Example 1 The passivation solution in Example 1 comprises: 10 wt% phosphoric acid, 4 wt% boric acid, 4 wt% light magnesium carbonate, 0.6 wt% disodium EDTA, and the balance being deionized water.

[0052] The organic insulating layer in Example 1 comprises: 25 parts of styrene, 35 parts of N-phenylmaleimide, 15 parts of fluorinated acrylate, and 1 wt% of azobisisobutyronitrile initiator, added to butyl acetate solvent to prepare a solution with a total monomer concentration of 0.6 mol / L. The fluorinated acrylate used is perfluorohexylethyl acrylate.

[0053] In the zirconium-magnesium composite nanofiller, the weight ratio of nano-zirconium oxide to nano-magnesium oxide is 5:1, and the particle size D50 of both is 100nm.

[0054] The fabrication of the integrally molded inductor in Example 1 includes the following steps: S10. Wash the ferrite magnetic powder with a particle size D50 of 50μm three times with deionized water and dry it in an oven at 80℃ for 2 hours. Immerse the dried ferrite magnetic powder in a passivation solution at a solid-liquid ratio of 1:4 and passivate it at a constant temperature of 55℃ for 25 minutes. Take out the magnetic powder, rinse it repeatedly with deionized water three times, and dry it in an oven at 85℃ for 2 hours. S20. After mixing the raw materials, the mixture is kept at 75℃ for 2 hours, then heated to 85℃ and kept at 85℃ for 2.5 hours to obtain a polymer solution with a solid content of about 30%. Five parts by weight of zirconium-magnesium composite nanofiller are weighed and added to the above polymer solution, and the mixture is dispersed by high-speed stirring for 40 minutes. Then, 100 parts by weight of the boron-phosphorus-magnesium ternary composite passivated metal magnetic powder obtained in step S10 are added, and the mixture is stirred for another 30 minutes. 80% of the solvent in the system is removed by rotary evaporation at 60℃. The metal magnetic powder coated with the adhesive is then placed in an oven at 120℃ for heat curing for 1.5 hours to obtain metal magnetic powder coated with an organic insulating layer. S30. Weigh 89 parts by weight of the metal magnetic powder obtained in step S20, 18 parts by weight of o-cresphenolic epoxy resin, 5 parts by weight of epoxy-modified silicone resin, and 0.2 parts by weight of leveling agent. Add them to a high-speed mixer and stir at room temperature for 25 minutes. Then add 3 parts by weight of aromatic amine latent curing agent diaminodiphenyl sulfone and continue stirring for 10 minutes. Pour the mixture into an inductor mold containing a winding coil and place it in a vacuum curing oven for pre-curing at 90°C and a vacuum degree of -0.095MPa for 1.5 hours. Then turn off the vacuum system and heat-cur at 155°C for 2 hours. After naturally cooling to room temperature, demold, remove burrs from the edges and clean the surface to obtain a one-piece molded inductor.

[0055] Example 2 Example 2 is based on Example 1, with the following differences: In Example 2, the monomer raw materials for the organic insulating layer are changed to: 20 parts styrene, 40 parts N-phenylmaleimide, and 10 parts fluorinated acrylate; and in step S30, the raw materials for preparing the magnetic core are changed to: 85 parts metal magnetic powder, 12 parts o-cresol formaldehyde epoxy resin, 4 parts epoxy modified silicone resin, and 2.5 parts aromatic amine latent curing agent.

[0056] Example 3 Example 3 is based on Example 1, with the following differences: In Example 3, no zirconium-magnesium composite nanofiller was added to the organic insulating layer.

[0057] Example 4 The difference between Example 4 and Example 1 is that in step S30, the o-cresol formaldehyde epoxy resin is replaced with an equal amount of epoxy-modified silicone resin.

[0058] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S10, the passivation solution does not contain boric acid and light magnesium carbonate, but is only an orthophosphoric acid solution (10wt%), that is, a single phosphate passivation layer is used instead of the boron-phosphorus-magnesium ternary composite passivation layer. The remaining steps and parameters are the same as in Example 1.

[0059] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step S20, the monomer raw materials for the organic insulating layer are changed to 60 parts of methyl methacrylate and 15 parts of fluorinated acrylate. The remaining steps and parameters are the same as in Example 1.

[0060] Performance testing (1) The inductance-temperature characteristics of the integral molded inductors prepared in Examples 1-4 and Comparative Examples 1-2 were tested: The inductor samples were placed in a high and low temperature test chamber with a temperature range of -55℃ to 200℃ and a heating rate of 2℃ / min. The inductance at different temperatures was measured using an LCR meter at 100kHz and 1.0V. The inductance retention rate at 180℃ was measured with the inductance at 25℃ as the reference.

[0061] (2) Core loss test of the integral molded inductors prepared in Examples 1-4 and Comparative Examples 1-2: The total core loss was measured using an AC magnetic performance test system under the conditions of 50mT and a frequency range of 100kHz.

[0062] (3) High-temperature insulation resistance test was performed on the integral molded inductors prepared in Examples 1-4 and Comparative Examples 1-2: The inductor samples were placed in a high-temperature chamber at 200℃ for 1 hour and the insulation resistance of the magnetic core was measured using an insulation resistance tester.

[0063] (4) Thermal shock test was performed on the integral molded inductors prepared in Examples 1-4 and Comparative Examples 1-2: 1000 cycles of thermal shock test were performed in accordance with the AEC-Q200 standard at -55℃ to 165℃. The inductance was measured before and after the test, the inductance change rate was calculated and the appearance was observed.

[0064] The measurement results are shown in Table 1.

[0065] Table 1

[0066] Analysis of Table 1 shows that the inductance retention rate of the inductor prepared in the examples is above 87% at 180℃, while that of the comparative examples is only maintained at 70%. This indicates that the boron-phosphorus-magnesium ternary composite passivation layer and the styrene-N-phenylmaleimide-fluorine modified acrylate ternary copolymer organic insulating layer of the present invention work synergistically to significantly improve the high-temperature stability of the inductor. The present invention constructs a high-temperature stable amorphous glassy interface through a boron-phosphorus-magnesium ternary composite inorganic passivation layer, combined with the high heat resistance and low dielectric properties of the ternary copolymer organic insulating layer, and the enhancement and modification of the organic insulating layer by zirconium-magnesium composite nanofillers, achieving a synergistic improvement in the high temperature resistance, low loss, and high reliability of the integrally molded inductor.

[0067] The above description is merely an exemplary embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A low-loss integrally molded inductor, characterized in that, It includes a winding coil and a magnetic core that encloses the winding coil, the magnetic core being made of a composite of metal magnetic powder and heat-resistant resin; The metal magnetic powder includes ferrite magnetic powder and an inorganic passivation layer and an organic insulating layer sequentially coated on the surface of the ferrite magnetic powder; wherein the organic insulating layer is obtained by copolymerization of styrene, N-phenylmaleimide and fluorinated acrylate.

2. The low-loss integrally molded inductor as described in claim 1, characterized in that, The inorganic passivation layer is prepared by a passivation solution, which comprises the following raw materials by mass fraction: Phosphoric acid: 8wt%~12wt%; Boric acid: 3wt%~5wt%; Light magnesium carbonate: 3wt%~5wt%; Disodium EDTA: 0.5wt%~1wt%; and deionized water.

3. The low-loss integrally molded inductor as described in claim 1, characterized in that, The organic insulating layer comprises the following raw materials in parts by weight: Styrene: 20-30 parts; N-phenylmaleimide: 30-40 parts; Fluorine-modified acrylate: 10-20 parts.

4. The low-loss integrally molded inductor as described in claim 1, characterized in that, The organic insulating layer also includes 3 to 7 parts by weight of zirconium-magnesium composite nanofiller; The zirconium-magnesium composite nanofiller comprises nano-zirconia and nano-magnesium oxide in a weight ratio of 3 to 8:

1.

5. The low-loss integrally molded inductor as described in claim 4, characterized in that, The particle size of the nano-zirconia is 50nm~300nm; And / or, the particle size of the nano-magnesium oxide is 50nm~300nm.

6. The low-loss integrally molded inductor as described in claim 1, characterized in that, The heat-resistant resin comprises the following raw materials in parts by weight: o-Cresol-formaldehyde epoxy resin: 15-25 parts; epoxy-modified silicone resin: 4-12 parts; aromatic amine latent curing agent: 2-4 parts; leveling agent: 0.5-1 part.

7. The low-loss integrally molded inductor as described in claim 1, characterized in that, The weight ratio of the metal magnetic powder to the heat-resistant resin is 8~10:2~3.

8. The low-loss integrally molded inductor as described in claim 1, characterized in that, The particle size of the ferrite magnetic powder is 10μm~300μm.

9. A method for preparing a low-loss integrally molded inductor according to any one of claims 1 to 8, characterized in that, The method for fabricating the low-loss integrally molded inductor includes the following steps: S10. Immerse the cleaned and dried ferrite magnetic powder in a passivation solution for passivation treatment, then remove and dry it. S20. Styrene, N-phenylmaleimide, fluorinated acrylate, initiator and solvent are mixed and copolymerized to obtain a polymer liquid; then zirconium magnesium composite nanofiller is added, stirred, and then ferrite magnetic powder treated in step S10 is added. Part of the solvent is removed by rotary evaporation and then cured by heating to obtain metal magnetic powder. S30. Mix o-cresol formaldehyde epoxy resin, epoxy modified silicone resin, leveling agent and metal magnetic powder obtained in step S20 evenly, then add aromatic amine latent curing agent, stir, pour into mold and pre-cur and heat-cur, demold to obtain the low loss integral molded inductor.

10. The method for fabricating a low-loss integrally molded inductor as described in claim 9, characterized in that, In step S10, the solid-liquid ratio of the passivation treatment is 1:4, the temperature is 50℃~60℃, the passivation time is 20min~30min, and the passivation is followed by drying at 80℃ for 2h~4h. And / or, in step S20, during the copolymerization reaction, the temperature is first maintained at 70℃~80℃ for 2h~3h, and then maintained at 80℃~90℃ for 2h~3h. And / or, in step S20, the heating and curing temperature is 110℃~120℃ and the curing time is 1h~2h; And / or, in step S30, the pre-curing temperature is 80℃~100℃, and the pre-curing time is 1h~3h; the heat curing temperature is 150℃~160℃, and the heat curing time is 1h~2h.